Corneal Confocal Microscopy: A Biomarker for Diabetic Peripheral Neuropathy - Ioannis N. Petropoulos (8748726) (2021)
Purpose Diagnosing early diabetic peripheral neuropathy remains a challenge due to deficiencies in currently advocated end points. The cornea is densely innervated with small sensory fibers, which are structurally and functionally comparable to intraepidermal nerve fibers. Corneal confocal microscopy is a method for rapid, noninvasive scanning of the living cornea with high resolution and magnification. Methods This narrative review presents the framework for the development of biomarkers and the literature on the use and adoption of corneal confocal microscopy as an objective, diagnostic biomarker in experimental and clinical studies of diabetic peripheral neuropathy. A search was performed on PubMed and Google Scholar based on the terms “corneal confocal microscopy,” “diabetic neuropathy,” “corneal sensitivity,” and “clinical trials.” Findings A substantial body of evidence underpins the thesis that corneal nerve loss predicts incident neuropathy and progresses with the severity of diabetic peripheral neuropathy. Corneal confocal microscopy also identifies early corneal nerve regeneration, strongly arguing for its inclusion as a surrogate end point in clinical trials of disease-modifying therapies. Implications There are sufficient diagnostic and prospective validation studies to fulfill the US Food and Drug Administration criteria for a biomarker to support the inclusion of corneal confocal microscopy as a primary end point in clinical trials of disease-modifying therapies in diabetic neuropathy. Other Information Published in: Clinical Therapeutics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clinthera.2021.04.003